The Influence of Online Customer Reviews, Online Customer Ratings, Cash on Delivery, Free Shipping Taglines, and Product Bundling on Purchase Decisions of Marina Products at the Official Shopee Store - Grecya Ho; Enrico Aziezy; Wisnu Wijayanto; Dian Safitri P Koesoemasari (Darul Yasin Al Sys, 2026)
The rapid growth of e-commerce in Indonesia has transformed consumer behavior in online purchasing decisions, particularly as consumers increasingly rely on informational and promotional signals before completing digital transactions. Previous studies on the effects of online customer reviews, online customer ratings, Cash on Delivery, free shipping taglines, and product bundling on purchasing decisions have produced inconsistent findings. This study aims to analyze the effects of online customer reviews, online customer ratings, Cash on Delivery, free shipping taglines, and product bundling on purchasing decisions for Marina products at the Shopee Official Store. This study employed a quantitative method with an explanatory research design. The population consisted of students from the Faculty of Economics and Business at Universitas Wijayakusuma Purwokerto who had purchased Marina products through the Shopee Official Store. Using purposive sampling, 100 respondents were selected as the research sample. Data were collected through Likert-scale questionnaires and analyzed using multiple linear regression analysis. The findings indicate that online customer reviews, online customer ratings, Cash on Delivery, free shipping taglines, and product bundling have positive and significant effects on purchasing decisions. Product bundling emerged as the most dominant factor influencing purchasing decisions, whereas Cash on Delivery had the lowest yet still significant effect. The coefficient of determination value of 76.9% indicates that the independent variables strongly explain variations in purchasing decisions. The study concludes that digital marketing strategies based on information quality, promotional incentives, and transaction security play important roles in strengthening consumer purchasing decisions on marketplace platforms. These findings contribute to digital marketing literature by clarifying the combined influence of consumer-generated information, payment security, and promotional strategies, while providing practical implications for companies to improve review quality, maintain product ratings, optimize free shipping promotions, strengthen Cash on Delivery services, and develop product bundling strategies aligned with consumer needs.